2017
DOI: 10.1038/s41467-017-01907-4
|View full text |Cite
|
Sign up to set email alerts
|

Future loss of Arctic sea-ice cover could drive a substantial decrease in California’s rainfall

Abstract: From 2012 to 2016, California experienced one of the worst droughts since the start of observational records. As in previous dry periods, precipitation-inducing winter storms were steered away from California by a persistent atmospheric ridging system in the North Pacific. Here we identify a new link between Arctic sea-ice loss and the North Pacific geopotential ridge development. In a two-step teleconnection, sea-ice changes lead to reorganization of tropical convection that in turn triggers an anticyclonic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 66 publications
8
91
2
Order By: Relevance
“…All of these features are consistent with most previous coupled modeling studies on this topic (Deser et al, , ; Tomas et al, ; Blackport & Kushner, , ; Oudar et al, ; Wang et al, 2017; Sun et al, ; Hay et al, ; Blackport & Screen, ). Note that our findings are distinct from those of Cvijanovic et al () who found increased geopotential height over the North Pacific and decreased precipitation over the west coast of the United States in response to Arctic sea ice loss. They speculated that the disparity between their results and previous studies is due to the method used to constrain sea ice.…”
Section: Implications For Coordinated Experiments In Pamipcontrasting
confidence: 99%
“…All of these features are consistent with most previous coupled modeling studies on this topic (Deser et al, , ; Tomas et al, ; Blackport & Kushner, , ; Oudar et al, ; Wang et al, 2017; Sun et al, ; Hay et al, ; Blackport & Screen, ). Note that our findings are distinct from those of Cvijanovic et al () who found increased geopotential height over the North Pacific and decreased precipitation over the west coast of the United States in response to Arctic sea ice loss. They speculated that the disparity between their results and previous studies is due to the method used to constrain sea ice.…”
Section: Implications For Coordinated Experiments In Pamipcontrasting
confidence: 99%
“…The prospects of climate change make such extreme drought events more likely in the future (Cvijanovic et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…We primarily present ensemble‐mean results but include the ensemble spread in the figures for reference. Unlike previous studies (Deser et al, ; Sun et al, ; Tomas et al, ; K. Wang et al, ), our modified‐albedo approach avoids using external heat flux anomalies to modulate the Arctic sea ice cover and thus ensures energy conservation in the climate system (Bitz et al, ; Blackport & Kushner, , ; Cvijanovic et al, ; Graversen & Wang, ; Scinocca et al, ; Screen et al, ).…”
Section: Observations Model Experiments and The Energetics Frameworkmentioning
confidence: 99%